2011
DOI: 10.1177/205891581100200207
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approaches to the Cryopreservation of Human Spermatozoa: History and Development of the Spermatozoa Vitrification Technology

Abstract: Cryobiology is very intensively applied in reproductive and veterinary medicine for preservation of gametes, embryos and reproductive tissues. Sub-zero temperatures combined with appropriate cryoprotective agents preserve the physiological and reproductive functions of the cells making long-term storage possible without loss of viability. With the use of cryoprotective agents it has become possible to develop cryopreservation techniques, such as the slow conventional freezing and vitrification that are in use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 123 publications
1
21
0
Order By: Relevance
“…Reed et al [17] reviewed laboratory and clinical data for all frozen embryo replacement cycles from 2012 to 2015 and concluded that vitrification was more effective, as indicated by higher survival in vitrified embryos compared to slow-cooling cryopreservation. Furthermore, vitrification is also reliable and simple to learn and implement in the laboratory while clinical pregnancy and implantation rates outcomes are similar [17], which is supported by other studies have [18][19][20].…”
Section: Is Vitrification Superior To Conventional Freezing?supporting
confidence: 60%
See 3 more Smart Citations
“…Reed et al [17] reviewed laboratory and clinical data for all frozen embryo replacement cycles from 2012 to 2015 and concluded that vitrification was more effective, as indicated by higher survival in vitrified embryos compared to slow-cooling cryopreservation. Furthermore, vitrification is also reliable and simple to learn and implement in the laboratory while clinical pregnancy and implantation rates outcomes are similar [17], which is supported by other studies have [18][19][20].…”
Section: Is Vitrification Superior To Conventional Freezing?supporting
confidence: 60%
“…Indeed, unlike the results noted above, using permeable cryoprotectants in sperm vitrification resulted in compromised or even lower motility than conventional freezing with permeable cryoprotectants [21][22][23]29] (Table 1). Isachenko et al [18,19] used 52 human swim up-prepared ejaculates for vitrification without permeable cryoprotectant. They found that in contrast to conventional freezing with glycerol, vitrified sperm displayed higher motility and integrity rates of cytoplasmic and acrosomal membranes, while no difference in spontaneous cryo-capacitation or acrosome reaction was observed [18].…”
Section: Cryoprotectants and Cryodevices In Sperm Vitrificationmentioning
confidence: 99%
See 2 more Smart Citations
“…For warming, the 0.5 mL straw is cut at one end, and the inside 0.25 mL straw falls out immediately in 5 mL of warming medium (commercial medium and 0.1% dextran) at a temperature of 37°C. Then, the sample is concentrated by centrifugation at 1800 rpm for 5 minutes, and afterward, the spermatozoa are resuspended in the desired volume according to the purpose of use (ART procedure such as IUI, IVF, or ICSI) 33,34,46 …”
Section: Research Carried Out On the Vitrification Technology Developmentioning
confidence: 99%